Association of leptin and leptin receptor polymorphisms with coronary artery disease in a North Chinese Han population - Wang,Haidong (2020)
Abstract INTRODUCTION: Leptin (LEP) is a peptide hormone that acts via leptin receptor (LEPR) binding. Genetic evidence from different human populations has implicated LEP/LEPR in the pathogenesis of coronary artery disease (CAD), and suggests that certain LEP/LEPR gene polymorphisms may increase the risk of CAD. The aim of this study was to assess two single nucleotide polymorphisms (SNPs) in LEP genes (rs2167270 and rs7799039) and two in LEPR genes (rs6588147, rs1137100) for association with CAD. METHODS: We enrolled 271 North Chinese Han CAD patients, and 113 healthy age- and sex-matched controls. Genomic DNA was extracted from whole blood, and the four SNPs were assessed using a MassArray system. RESULTS: The G allele frequency at rs2167270 was significantly higher among CAD cases than among controls. The AG genotype at rs7799039 was associated with a significantly decreased risk of CAD unlike the AA genotype used as the reference. The A allele was significantly associated with the CAD patient group. Interestingly, statistically significant differences in genotype and allele frequency at LEP rs2167270 and rs7799039 existed among females but not among males. CONCLUSIONS: The current study detected a significant association between genetic variations at LEP rs7799039 and rs2167270 and the risk of CAD in a north Chinese population, and revealed that LEP rs2167270 and rs7799039 gene polymorphisms might act as predisposing factors for CAD.